U-slot Circular Patch Antenna for WLAN Application - Arshad Wahab; Jiadong Xu (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
A dual-frequency microstrip patch antennas has been presented and used for 802.11WLAN applications. The antennas had been designed, simulated and parametrically studied in CST Microwave studio. By introducing u-slot, dual-band operation with its operating mode centered at frequency 2.4GHz, 3.65GHz and 5.2GHz had been obtained. The gain and directivity had been improved by adjusting the parameters of the antennas. The gain of the proposed designs was 6.019dBi, 4.04dBi and 6.22dBi and directivity was 6.02dBi, 4.05dBi and 6.22dBi at resonant frequencies 2.4GHz, 3.6GHz and 5.2GHz respectively. The patch antennas had been proposed to be used in portable devices that require miniaturized constituent parts. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7479